Communication and trans intelligibility: Reflections on the movements of transvestite subjects in the claim of citizenship and construction of other possible worlds - Santos, Luan Correia Cunha (Seven Editora, 2023)
In this work, we seek to problematize gender roles as social constructions forged and reiterated in the repetitions of the technologies that form them, understanding that these act in a systematic and institutionalized way from the family, the school, the State, in the private and public spheres. With this, we reflect how the movement of subjects who move between genders seeks the recognition of their identities and the claim of citizenship, as well as how the (re)existence of these helps us to think of other constructions of possible realities, less violent and ignorant of diversity. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-150